“Burying” covered coronary stents under drug-eluting stents: A novel approach to ensure long-term stent patency - Bossard, Matthias; Cioffi, Giacomo Maria; Yildirim, Mustafa; Moccetti, Federico; Wolfrum, Mathias; Attinger, Adrian; Toggweiler, Stefan; Kobza, Richard; Cuculi, Florim (Cardiology journal, 2023)
Covered coronary stent (CS) implantation is associated with a high risk for in-stent restenosis (ISR) and stent thrombosis (ST). We describe the outcomes after overstenting ("burying") CS using contemporary drug-eluting stents (DES). We analyzed short- and long-term outcomes of consecutive patients who had had a CS implanted, which was consecutively covered ("buried") with a third-generation DES. CSs were primarily post-dilated and then covered with a longer DES overlapping the proximal and distal edges of the CS. To ensure optimal stent expansion and appositions, all lesions were post-dilated using adequately sized non-compliant balloons. Between 2015 and 2020, 23 patients (mean age 67 ± 14 years, 74% males) were treated using this novel approach. Reasons for implanting CS included treatment of coronary aneurysms (n = 7; 30%), coronary perforations (n = 13; 57%), and aorto-ostial dissections (n = 3; 13%). All CSs were successfully deployed, and no peri-procedural complications occurred. The median time of follow-up was 24.5 (interquartile range [IQR] 11.7-37.9) months. All patients had a 1-month follow-up (FU) and 19/23 (83%) patients had 12-month FU (FU range 1-60 months). No probable or definite STs occurred, and no cardiovascular deaths were observed. Among patients undergoing angiographic FU (11/23 [48%]), 1/23 showed angiographically significant ISR 6 months post CS implantation. Burying a coronary CS under a DES appears to be a safe and promising strategy to overcome the limitations of the currently available CS devices, including a relatively high risk for target lesion failure due to ISR and ST.